INTERVISTA A MARCO NISI - MediaGEO, Redazione (GEOmedia, 2022)
We interviewed Marco Nisi, Aerospace Engineer currently employed as a consultant for project management activities coordinating European consortia with a main focus on satellite communication (SATCOM) and navigation (NAVCOM) applied to the energy, security, aeronautics and maritime sectors.